Student Engagement and English Language Skills Development through Activity-Based Learning in English Preparation Course - Sucharitrak, Suphatra; Seenon, Udomkrit; Cullen, Robert; Salarat , Parichart; Jampathip, Nida (วารสารนวัตกรรมการจัดการศึกษาและการวิจัย, 2026)
This article aimed: (1) to assess whether activity-based instructional tasks improved students’ language skills, (2) to examine the extent to which the tasks influenced students’ learning engagement and behavioral patterns, and (3) to explore students’ perceptions and experiences of the course design. A mixed methods approach was used. Quantitative data were collected through pre- and post-tests covering five language skill areas and analyzed using paired-sample t-tests. Qualitative data came from course reflection forms using a five-point Likert scale and semi-structured interviews with 30 students, analyzed through thematic analysis. Participants were 125 first-year undergraduate English major students enrolled in five parallel course sections. The results showed statistically significant improvement in all five language skill areas. The overall post-test mean score increased from 27.22 to 34.92 (t = -21.201, p < .001, n = 125). The greatest gain was in grammatical structure (+1.85), followed by reading and writing (+1.72) and listening and speaking (+1.57). Student self-assessment of engagement and collaboration was high, with a total mean of 4.32 out of 5.00 (SD = 0.48). The highest score was in collaboration in groups (M = 4.64). Interview data showed that group work, positive teacher feedback, and game-based activities were the main factors that supported student confidence and participation. Activity-based learning is effective for improving English language skills and promoting student engagement in university EFL preparatory courses. EFL teachers and course designers should use collaborative, interactive, and task-based instruction to support both language development and active student participation.